Muallaf Center Design as an Implementation of Psycological and Economical Effect for Muallaf in Malaysia - Yudha, Ansfiksia Eka Poetra; setiyowati, ernaning (Journal of Islamic Architecture, 2016)
Mualaf is the term to represent people who just moves to Islam from other religion. Mualaf Center is an important place for mualaf to get information about Islam. There are some reasons and factors that make a not-Moslem hesitates about their religion and decides to move to Islam.Â  These circumstances make them need a psychological and economical guidance as the effects after they become mualaf. There are 6.3% from total citizen becomes mualaf in Malaysia. This number is in the not-Moslem society, so the effect of becoming mualaf can be perceived especially the psychological and economical effects. Therefore, mualaf center can be a good place for mualaf to get a guidance and consultation. This paper discusses mualaf center design based on the issues and problems about mualaf in Malaysia. The aim of this study is to find a recommendation design for mualaf center based on the issue in Malaysia. The discussion uses literature study method which will be analyzed descriptively. So the result of the discussion is a summary of design criteria that proper with the issue. This design criterion will be integrated using relevant design theme approach, i.e. sustainable architecture. The design criteria that is already integrated is the availability of guidance and consultation facilities, also entrepreneur practice facility toward psychological and economical effects. With by the guidance in this mualaf center, the mualaf will be capable of adapting to the social environment around them and also can rebuild their economic life as before in islamic ways.